Tocilizumab-coated solid lipid nanoparticles loaded with cannabidiol as a novel drug delivery strategy for treating COVID-19: A review - Zielińska, Aleksandra; Eder, Piotr; Karczewski, Jacek; Szalata, Marlena; Hryhorowicz, Szymon; Wielgus, Karolina; Szalata, Milena; Dobrowolska, Agnieszka; Atanasov, Atanas G.; Słomski, Ryszard; Souto, Eliana B. (Frontiers in Immunology, 2023)
Commonly used clinical strategies against coronavirus disease 19 (COVID-19), including the potential role of monoclonal antibodies for site-specific targeted drug delivery, are discussed here. Solid lipid nanoparticles (SLN) tailored with tocilizumab (TCZ) and loading cannabidiol (CBD) for the treatment of COVID-19 by the oral route are proposed. TCZ, as a humanized IgG1 monoclonal antibody and an interleukin-6 (IL-6) receptor agonist, can attenuate cytokine storms in patients infected with SARS-CoV-2. In contrast, CBD (an anti-inflammatory cannabinoid and TCZ agonist) alleviates anxiety, schizophrenia, and depression. The high amount of CBD from Cannabis sativa L. can modulate gene expression and inflammation and harbor anti-cancer and anti-inflammatory properties. Still, it may modulate angiotensin-converting enzyme II (ACE2) expression in SARS-CoV-2 target tissues. It has already been proven that immunosuppressive drugs targeting the IL-6 receptor may ameliorate lethal inflammatory responses in COVID-19 patients. TCZ, as an immunosuppressive drug, is mainly used to treat rheumatoid arthritis, although several attempts have been made to use it in the active hyperinflammatory phase of COVID-19, with favorable outcomes. TCZ is currently administered intravenously. This review proposes TCZ-tailored CBD-loaded SLN as a vaccine platform for managing SARS-CoV-2 and related infections.